A Structured Transfer of Care Process Reduces Perioperative Complications in Cardiac Surgery Patients. (August 2017) - Hall, Michael; Robertson, Jamie; Merkel, Matthias; Aziz, Michael; Hutchens, Michael
Abstract : INTRODUCTION: Serious complications are common during the intensive care of postoperative cardiac surgery patients. Some of these complications may be influenced by communication during the process of handover of care from the operating room to the intensive care unit (ICU) team. A structured transfer of care process may reduce the rate of communication errors and perioperative complications. METHODS: We hypothesized that a collaborative, comprehensive, structured handover of care from the intraoperative team to the ICU team would reduce a specific set of postoperative complications. We tested this hypothesis by developing and introducing a comprehensive multidisciplinary transfer of care process. We measured patient outcomes before and after the intervention using a linkage between 2 care databases: an Anesthesia Information Management System and a critical care complication registry database. RESULTS: There were 1127 total postoperative cardiac surgery admissions during the study period, 550 before and 577 after the intervention. There was no statistical difference between overall complications before and after the intervention ( P = .154). However, there was a statistically significant reduction in preventable complications after the intervention ( P = .023). DISCUSSION: The main finding of this investigation is that the introduction of a collaborative, comprehensive transfer of care process from the operating room to the ICU was associated with patients suffering fewer preventable complications. Abstract : Supplemental Digital Content is available in the text.Published ahead of print May 11, 2017.